Lower limb linear morphoea in a pregnant woman with known Graves' disease and cytomegalovirus immunoglobulin M positivity. (9th April 2014) - Wong, Brittany; Piliouras, Peter; Mortimore, Rohan; Zonta, Mark; Tucker, Simon
Abstract: We report a case of linear morphoea in a 21‐year‐old woman with known Graves' disease who was also cytomegalovirus (CMV) IgM‐positive and in her early first trimester of pregnancy. The histopathology showed hyalinisation of the dermis with perivascular superficial and deep lymphocytic infiltrates extending into the septae of the subcutis and impinging on adjacent lobules; there was also fibrosis of the subcutis. Magnetic resonance imaging showed T2 high intensity of the subcutaneous tissue and intermuscular planes of the thigh and leg. It is well known that morphoea can follow pregnancy and thyroid disease and that CMV is postulated to contribute in some patients. This case highlights a combination of risk factors for this disease that have not been reported collectively in the literature to our knowledge.